1999
DOI: 10.1016/s1072-7515(98)00259-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Nitric Oxide in Ischemia and Reperfusion Injury of the Liver

Abstract: Background: The suppressed production of nitric oxide (NO), associated with endothelial dysfunction, is thought to be a cause of ischemia and reperfusion injury of the liver. But findings of the salutary effects of NO enhancement on such injury have been conflicting. In this study, we tested our hypothesis that NO enhancement would attenuate ischemic liver injury. For this purpose, an NO precursor, L-arginine, and a novel NO donor, FK409, were applied to a 2-hour total hepatic vascular exclusion model in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 44 publications
5
29
1
3
Order By: Relevance
“…Consistent with prior reports [4,33,34], we observed greater sinusoidal congestion and a greater presence of PMNs in the non-preconditioned group. Necrosis, on the other hand, was similar between groups.…”
Section: Figsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with prior reports [4,33,34], we observed greater sinusoidal congestion and a greater presence of PMNs in the non-preconditioned group. Necrosis, on the other hand, was similar between groups.…”
Section: Figsupporting
confidence: 92%
“…The significant reduction of AST levels measured 3 hours after reperfusion reflected the beneficial effects of preconditioning treatment in this in vivo I/RI model, which is consistent with previous studies [6,13,17,33,34]. The serum level of AST was distinctly elevated in both groups subjected to I/RI.…”
Section: Figsupporting
confidence: 90%
See 2 more Smart Citations
“…In the current study, we found that Rb1 post-treatment significantly reduced hepatic ICAM-1 mRNA levels during early reperfusion periods, and suppressed neutrophil accumulation in liver. These findings are consistent with previous reports that inhibition of NO synthesis increased ICAM-1 expression and enhanced neutrophildependent reperfusion injury in hepatic warm I/R injury (Liu et al, 1998) and that NO enhancement attenuated neutrophil infiltration and hepatic warm I/R injury (Shimamura et al, 1999). Therefore, upregulated NO by Rb1 post-treatment might also have a role in modulating the inflammatory process by decreasing the expression of TNF-α and ICAM-1.…”
Section: Discussionsupporting
confidence: 93%